Expression of mRNA for 5-HT2 Receptors and Proteins Related to Inactivation of 5-HT in Mouse Osteoblasts - Takao Hirai; Kohji Tokumo; Daijyu Tsuchiya; Hiroaki Nishio (Elsevier, 2009)
We analyzed the expression of 5-HT2 receptors and proteins related to inactivation of 5-HT in primary cultures of mouse osteoblasts. The mRNA for the 5-HT2A receptor was detectable in anaplastic osteoblasts as well as in differentiated and matured osteoblasts. The mRNA for the 5-HT2B receptor and 5-HT transporter was undetectable in anaplastic osteoblasts and became detectable in differentiated and matured osteoblasts. It was suggested that 5-HT might regulate the proliferation of anaplastic osteoblasts through the 5-HT2A receptor without control by 5-HT-inactivating mechanisms. The differentiation and maturation of osteoblasts might be regulated by the activation of the 5-HT2B receptor under the control of 5-HT inactivation. Keywords:: osteoblast, 5-HT2 receptor, 5-HT transporter (5-HTT)